37‐3: A Novel Pixel Structure for 847 ppi Display with LTPS Technology. Issue 1 (May 2016) - Ma, Yangzhao; Ikeno, Hidenori; Shen, Poping; Wu, Ling; Wu, Hao; Song, Qiong; Tseng, Changho
Abstract : We propose a new pixel design which has one slit electrode for 847 ppi resolution. The pixel design facilitates a reduction of disclination area in the pixel and reduction of color mixing. As a result, we have demonstrated a high luminance, small color shift until the 30 degrees view angle and good image quality on 5.2 inch 847 ppi panel.